PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS PADA INDUSTRI PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rizka Dwi Haryanti; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted to examine the effects of capital structure on profitability in the Pulp and Paper company listed on the Indonesia Stock Exchange. That is indicated by the capital structure Debt to Equity Ratio (DER) and Debt to Total Assets Ratio (DR) With the indicated profitability Return on equity (ROE) and Return on Assets (ROA). The study population was Pulp and Paper Industry company listed in Indonesia Stock Exchange during the period 2008-2013. In the financial statement lists the value of financial ratios that will include DR, DER, ROE and ROA. Which have fluctuated financial statements during the period 2008-2013. Obtained a total sample of 36 financial statements of companies acquired through a sampling technique is purposive sampling.analytical technique data used is multiple linear regression and hypothesis testing using t-statistic, to examine the relationship with correlation, and the coefficient of determination to test the effect of DR, DER to ROE DR and DER to ROA using the program SPSS.From the results of the analysis showed that DR, DER no significant effect on ROE by t tests where -0.894> -2.032 contributions DR, DER to ROE of 2.4%, while the remaining 97.6%. whereas DR, DER does not significantly influence the outcome ROA 0.968> 2.032. With the contribution of DR, DER to ROA of 10.8% while the remaining 89.2% is influenced by factors other than factors of capital structure.Keywords: Capital Structure, Profitability